Pengaruh Perlakuan Pemangkasan Dan Pemberian Pupuk Solid Terhadap Pertumbuhan Dan Produksi Tanaman Kedelai (Glycine max L. Merril) - Mahdalena Mahdalena; Abdul Rofik; Tiara Sartika Sari (Universitas Widya Gama Mahakam, 2018)
Soybean is an important food crop after rice and corn. Soybean production in East Kalimantan based on the 2014 forecast rate is estimated at 1,263 tons of dry seeds. Compared to 2013 production (ATAP 2013) there was a decrease of 139 tons (9.91%) (BPS, 2014). The low productivity is because the technique of managing soybean plants is still not optimal. Efforts to increase soybean productivity can be done by conducting intensive cultivation techniques. One of the cultivation techniques that can be done is by technical methods, namely crop trimming and intensive agricultural cultivation can be done in various ways including fertilization. The study was carried out for 5 months, namely from January to May 2018. The research site was on experimental land owned by the Faculty of Agriculture, Widya Gama Mahakam Samarinda. This study used a Randomized Block Design (RBD) with a 2 x 3 factorial experiment consisting of 3 replications. The first factor is Pruning which consists of 2 levels: namely p0 (without pruning), p1 (vegetative phase V4 pruning). The second factor is the dose of Solid fertilizer consists of 3 levels, namely s0 (without fertilization), s1 (5 kg / plot), s2 (10 kg / plot). The results showed that the pruning (P) treatment had a significant effect on the parameters of the number of productive branches and had no significant effect on height, flowering age, number of pods, weight of 100 seeds, weight of crop seeds and weight of mapped seeds. While giving Solid (S) fertilizer does not significantly affect all parameters. But the interaction of the treatment of pruning and giving Solid (PS) significantly affected the parameters of the number of productive branches.